Ontogenetic Development of Vestibulo-Ocular Reflexes in Amphibians - Branoner, Francisco; Chagnaud, Boris P.; Straka, Hans (Frontiers in Neural Circuits, 2016)
Vestibulo-ocular reflexes ensure gaze stability during locomotion and passively induced head/body movements. In precocial vertebrates such as amphibians, vestibular reflexes are required very early at the onset of locomotor activity. While the formation of inner ears and the assembly of sensory-motor pathways is largely completed soon after hatching, angular and translational/tilt vestibulo-ocular reflexes (VOR) display differential functional onsets and mature with different time courses. Otolith-derived eye movements appear immediately after hatching, whereas the appearance and progressive amelioration of semicircular canal-evoked eye movements is delayed and dependent on the acquisition of sufficiently large semicircular canal diameters. Moreover, semicircular canal functionality is also required to tune the initially omnidirectional otolith-derived VOR. The tuning is due to a reinforcement of those vestibulo-ocular connections that are co-activated by semicircular canal and otolith inputs during natural head/body motion. This suggests that molecular mechanisms initially guide the basic ontogenetic wiring, whereas semicircular canal-dependent activity is required to establish the spatio-temporal specificity of the reflex. While a robust VOR is activated during passive head/body movements, locomotor efference copies provide the major source for compensatory eye movements during tail- and limb-based swimming of larval and adult frogs. The integration of active/passive motion-related signals for gaze stabilization occurs in central vestibular neurons that are arranged as segmentally iterated functional groups along rhombomere 1-8. However, at variance with the topographic maps of most other sensory systems, the sensory-motor transformation of motion-related signals occurs in segmentally specific neuronal groups defined by the extraocular motor output targets.